Implementing Service Learning Method in Object-Based Arabic Mufradat Learning at Madrasah Ibtidaiyah Swasta Al-Ikhlas, Naga Timbul Village: A Participatory Action Research Approach - Andri Rivai; Fian Triadi; Hasibuan, Muhammad Syarif Muda; Muhajirah Binti Jamaluddin; Siregar, Ali Sohot; Bagas Pranomo; Radya Fauzan (ASSUNNAH PRESS, 2025)
Arabic language learning at the Madrasah Ibtidaiyah level faces significant challenges in vocabulary (mufradat) acquisition, particularly in rural areas with limited educational resources. This study examines the effectiveness of implementing an object-based Service Learning method to enhance mufradat mastery at Madrasah Ibtidaiyah Swasta Al-Ikhlas, Naga Timbul Village, Tanjung Morawa District, through a Participatory Action Research approach integrated with Maqasid Shariah principles. The research employed a mixed-methods design with PAR cycles encompassing participatory planning, collaborative implementation, systematic observation, and critical reflection. Eleven students from grades IV-V participated in an intensive five-day Arabic language halaqah program facilitated by university students during their community service (KKNT). Data collection instruments included daily vocabulary tests, participatory observation, in-depth interviews, and visual documentation. Quantitative findings revealed a consistent 100% achievement rate in mastering five new vocabulary items daily throughout the program, with an overall retention rate of 95.4%. Qualitative analysis demonstrated significant transformation in students' affective dimensions, marked by increased active participation, linguistic confidence, and intrinsic motivation. The concrete object-based approach, combined with talaqqi techniques, educational games, and contextual practice, proved effective in constructing strong semantic associations. The integration of Maqasid Shariah principles manifested in achieving hifz ad-din through strengthening the language of revelation, hifz al-'aql through intellectual capacity development, and hifz an-nasl through Quranic generation formation. Time constraints were addressed through strategic collaboration with madrasah teachers to ensure program sustainability. This research contributes to developing a holistic Arabic language learning model that integrates cognitive, affective, social, and spiritual dimensions aligned with Indonesian Islamic education characteristics.